Evidence for possible non‐canonical pathway(s) driven early‐onset colorectal cancer in India. Issue 1 (20th November 2012) - Raman, Ratheesh; Kotapalli, Viswakalyan; Adduri, Raju; Gowrishankar, Swarnalata; Bashyam, Leena; Chaudhary, Ajay; Vamsy, Mohana; Patnaik, Sujith; Srinivasulu, Mukta; Sastry, Regulagadda; Rao, Subramanyeshwar; Vasala, Anjayneyulu; et al.
Abstract Two genetic instability pathways viz. chromosomal instability, driven primarily by APC mutation induced deregulated Wnt signaling, and microsatellite instability (MSI) caused by mismatch repair (MMR) inactivation, together account for >90% of late‐onset colorectal cancer (CRC). Our understanding of early‐onset sporadic CRC is however comparatively limited. In addition, most seminal studies have been performed in the western population and analyses of tumorigenesis pathway(s) causing CRC in developing nations have been rare. We performed a comparative analysis of early and late‐onset CRC from India with respect to common genetic aberrations including Wnt, KRAS, and p53 (constituting the classical CRC progression sequence) in addition to MSI. Our results revealed the absence of Wnt and MSI in a significant proportion of early‐onset as against late‐onset CRC in India. In addition, KRAS mutation frequency was significantly lower in early‐onset CRC indicating that a significant proportion of CRC in India may follow tumorigenesis pathways distinct from the classical CRC progression sequence. Our study has therefore revealed the possible existence of non‐canonical tumorigenesis pathways in early‐onset CRC in India. © 2012 Wiley Periodicals, Inc.